Frequency of temporomandibular joint dysfunction with clicking symptom due to primary molar premature loss in children aged 6-12 years old - Laksitowati, Riana Hestu (Padjadjaran Journal of Dentistry, 2009)
Temporomandibular joint dysfunction with clicking symptom is sound “click” when open and close the mouth. The purpose of this study was to obtain the description of the frequency of temporomandibular joint dysfunction with clicking symptom caused by premature loss of primary molar teeth in children aged 6-12 years old at SDIT Imam Bukhari. The study was a descriptive survey, 136 students as samples were taken by purposive sampling technique. Premature loss of primary molar teeth examined by checking up the first and second primary molars upper and lower jaw using the hand mirror and explorer. Temporomandibular joint dysfunction examined by palpation and using a stethoscope. The result of this study showed that from 136 students having premature loss there are 49 students (36,03%) had temporomandibular joint dysfunction with clicking symptom. The conclusion of this study indicates that more than one-fourth students at SDIT Imam Bukhari with premature loss of primary molar teeth had temporomandibular joint dysfunction with clicking symptom.